Fibroblast growth factor signaling in axons: from development to disease - Tomé, Diogo (2023)
The fibroblast growth factor (FGF) family regulates various and important aspects of nervous system development, ranging from the well-established roles in neuronal patterning to more recent and exciting functions in axonal growth and synaptogenesis. In addition, FGFs play a critical role in axonal regeneration, particularly after spinal cord injury, confirming their versatile nature in the nervous system. Due to their widespread involvement in neural development, the FGF system also underlies several human neurological disorders. While particular attention has been given to FGFs in a whole-cell context, their effects at the axonal level are in most cases undervalued. Here we discuss the endeavor of the FGF system in axons, we delve into this neuronal subcompartment to provide an original view of this multipurpose family of growth factors in nervous system (dys)function. Video Abstract.